PVP-coated silver nanoparticles showing antifungal improved activity against dermatophytes - Silva, Stephane Edgar da (2018)
Fungal infections affecting human beings have increased during the last years and the currently available treatments, when administered for long periods, trigger microbial resistance. Such demands the development of new viable therapeutic alternatives. Silver is known since the antiquity by its antimicrobial properties and, herein, it was used to produce two types of nanoparticles (NPs), uncoated and coated with polyvinylpyrrolidone (PVP), which were aimed to be used in fungal infection treatment. NPs properties were characterized by Transmission electron microscopy, X-ray diffraction, UV–Vis, Dynamic light scattering, Fourier transform infrared, and Energy-dispersive X-ray spectroscopy. Furthermore, in vitro studies were also performed to evaluate NPs cytotoxic profile and antifungal activity. The results obtained revealed that the produced nanoparticles are biocompatible and have a good potential for being used in the treatment of common skin infections caused by Trichophyton rubrum and Trichophyton mentagrophytes, being PVP-coated silver NPs the most suitable ones.